2014
DOI: 10.1007/s11270-013-1846-0
|View full text |Cite
|
Sign up to set email alerts
|

Decolourisation of Different Dyes by two Pseudomonas Strains Under Various Growth Conditions

Abstract: The aim of the present study was the decolourisation of mixture of two dyes belonging to different groups by two Pseudomonas fluorescens strains (Sz6 and SDz3). Influence of different incubation conditions on decolourisation effectiveness was evaluated. Dyes used in the experiment were diazo Evans blue (EB) and triphenylmethane brilliant green (BG). Another goal of the experiment was the estimation of toxicity of process by-products. Incubation conditions had a significant influence on the rate of decolourisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
(112 reference statements)
5
23
0
1
Order By: Relevance
“…The main experiment was performed using the same method as in our previous study on Pseudomonas strains (Zabłocka-Godlewska et al 2014 ). For this part of the experiment, the dye concentrations were selected based on the results of the concentration test (0.05 g l −1 for Evans blue; 0.1 g l −1 for brilliant green; 0.08 g l −1 for the mixture).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main experiment was performed using the same method as in our previous study on Pseudomonas strains (Zabłocka-Godlewska et al 2014 ). For this part of the experiment, the dye concentrations were selected based on the results of the concentration test (0.05 g l −1 for Evans blue; 0.1 g l −1 for brilliant green; 0.08 g l −1 for the mixture).…”
Section: Methodsmentioning
confidence: 99%
“…For the mixture, Evans blue and brilliant green were prepared in a ratio of 1:1 (0.04 g l −1 of BG and 0.04 g l −1 of EB). Identically to the previous case (Zabłocka-Godlewska et al 2014 ), the cultures were incubated in different conditions (static, semistatic and shaken). The shaken samples were shaken on a rotary shaker for 24 h day −1 (200 rpm); the semistatic samples were shaken with the same speed as the shaken samples every other day.…”
Section: Methodsmentioning
confidence: 99%
“…Dye mixture concentration had a significant impact on bacterial decolourization results. A concentration of dyes in solution that is too high may be toxic for microorganisms and may decrease decolourization efficiency (Pearce et al 2003;Zabłocka-Godlewska et al 2014. On the other hand, it has been reported that dye concentration that is too low may negatively influence the recognition of dyes by enzymes and may similarly decrease decolourization efficiency (Meerbergen et al 2018;Pearce et al 2003).…”
Section: Influence Of Dye Mixture Concentration On Decolourization Efmentioning
confidence: 99%
“…However, biotransformation processes may also lead to the formation of toxic metabolites. The efficiency of the process, mechanisms involved, and the possibility of toxic metabolite formation all depends on what bacterial strains are used, the process conditions, the structure and concentration of dyes, and the composition of the dye mixture (Ali 2010;Kuhad et al 2012;Meerbergen et al 2018;Przystaś et al 2012Przystaś et al , 2015Saratale et al 2011;Solis et al 2012;Srinivasan and Viraraghavan 2010;Zabłocka-Godlewska et al 2014. It should be emphasized that in the bioreactors "pH" and "pH+sm" inoculated with the Abs37, dyes removal was most efficient, however the supplementation with nutrients combined with pH correction lead to an increase of the concentration of metabolites (high peak with max.…”
Section: Dye Mixture Removal By Pure Bacterial Culturementioning
confidence: 99%
See 1 more Smart Citation